IMPROVING THE ORGANIZATIONAL AND ECONOMIC ASPECTS OF FARMS SPECIALIZING IN HORTICULTURE - Dadaboev Tulkinjon Yusupjonovich (International Engineering Journal For Research & Development, 2020)
The article develops scientific proposals and practical recommendations aimed at preventing losses through the development of quality storage, transportation and sale of fruits to increase the demand for fruits grown in the country.